Evaluation of serum IL 18 / IL 18 binding protein ratio and their relation with IL- 18 gene polymorphisms in sample of Iraqi type 2 diabetes mellitus patients. A case control study - Osamah Abdulhussien Razooqi; Haider Faisal Ghazi; Mahmood Shakir Khudair (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate the ratio of interleukin18 and interleukin18 binding protein in type 2 diabetes mellitus patients, and its relation with the presence of interleukin18-607C/A and interleukin18-137G/C gene polymorphisms and the type of complications. Method: The case-control study at the endocrinology clinic of the Madinat Al-Imamin Al-Kazemin Teaching Hospital, Iraq, from September 2020 to July 2021, and comprised diagnosed patients type 2 diabetes mellitus, and healthy controls matched for age and gender. Blood samples were obtained that were processed for serum separation. Serum interleukin18 and interleukin18 binding protein levels were assessed, and part of the sample was used for deoxyribonucleic acid extraction using tetra-primer amplification refractory mutation system polymerase chain reaction with four specific primers for interleukin18-607C/A and interleukin-18-137G/C gene polymorphisms in both the groups. Data was analysed using SPSS 20. Results: Of the 168 subjects, 86(51.2%) were patients; 67(77.9%) females and 19(22.1%) males with mean age 52±8.97 years. There were 82(48.8%) controls; 56(68.3%) females and 26(31.7%) males with mean age 48±9.44 years (p>0.05). Higher serum level of interleukin18 and lower level of interleukin18 binding protein were seen in type 2 diabetes mellitus group compared to the controls (p<0.001). Interleukin18-137G/C and interleukin18-607C/A mutant alleles had odd ratios 3.52 (confidence interval: 1.91- 6.63) and 3.25 (confidence interval: 1.77-5.83), respectively, as risk factors for the occurrence of type 2 diabetes mellitus. There was an association of interleukin18-137G/C homozygous mutant genotype with the occurrence of retinopathy among type 2 diabetes mellitus patients (p=0.046), but risk allele C was not associated with retinopathy (p>0.05). Conclusions: The presence of interleukin18-137G/C and interleukin18-607C/A gene polymorphism might be considered a risk factor for type 2 diabetes mellitus. Key Words: Alleles, Interleukin, Diabetes, Genotype, Polymerase, DNA, Retinal, Mutation